2012
DOI: 10.1111/j.1439-0434.2012.01949.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Differentially Expressed Proteins in Resistant Soybean Leaves after Phakopsora pachyrhizi Infection

Abstract: Soybean rust caused by Phakopsora pachyrhizi is a destructive foliar disease in nearly all soybean‐producing countries. Understanding the host responses at the molecular level is certainly essential for effective control of the disease. To identify proteins involved in the resistance to soybean rust, differential proteomic analysis was conducted in soybean leaves of a resistant genotype after P. pachyrhizi infection. A total of 41 protein spots exhibiting a fold change >1.5 between the non‐inoculated and P. pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
0
8
0
5
Order By: Relevance
“…Although molecular studies are being conducted on this pathosystem, there is still little information on the molecular basis of this interaction [21,[24][25][26]. To develop rust-resistant soybean cultivars, a better understanding of the molecular basis and essential genes involved in defense responses is a key to control this disastrous disease [21]. As a result of this interaction, twelve differentially accumulated proteins were detected and identified in this study.…”
Section: Protein Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although molecular studies are being conducted on this pathosystem, there is still little information on the molecular basis of this interaction [21,[24][25][26]. To develop rust-resistant soybean cultivars, a better understanding of the molecular basis and essential genes involved in defense responses is a key to control this disastrous disease [21]. As a result of this interaction, twelve differentially accumulated proteins were detected and identified in this study.…”
Section: Protein Extractionmentioning
confidence: 99%
“…Understanding the host responses at the molecular level is certainly essential for effective control of the disease, and the molecular basis for rust resistance remained largely unknown in soybean [21]. The study of soybean genes that are differently expressed as a response to P. pachyrhizi can aid the identification of important genes involved in the resistance response and provide tools for genetic breeding programs for creation of soybean cultivars resistant to ASR [22,23].…”
Section: Protein Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, a few proteomic studies have examined the soybean proteome in response to ASR (6,22,35,40) and proteome of ASR (21,35). Based upon these studies, many genes have been identified that are possibly involved in the defense response to ASR.…”
Section: Introductionmentioning
confidence: 99%
“…Based upon these studies, many genes have been identified that are possibly involved in the defense response to ASR. Wang et al (40) used resistant soybean genotype to identify the differentially expressed proteins whereas Park et al (2013, unpublished) used two resistant and two susceptible soybean genotypes which are of different genetic background. In order to increase the chance of identifying true rust resistance associated proteins, we selected a pair of recombinant inbred lines that were segregating for rust resistance in the present study.…”
Section: Introductionmentioning
confidence: 99%